Clinical significance of mean platelet volume/lymphocyte ratio and mean platelet volume/platelet ratio in the exacerbation of chronic obstructive pulmonary disease - Özsarı, Emine; Koçak, Mehmet Zahid (The European Research Journal, 2019)
Objectives: Studies showing the role of systemic inflammation in chronic obstructive pulmonary disease (COPD) are increasing. Particularly, importance of mean platelet volume (MPV) and neutrophil/lymphocyte ratio (NLR) for acute exacerbation of COPD has been reported. The use of MPV/lymphocyte ratio (MLR) and MPV/platelet ratio(MPR) in acute exacerbation of COPD patients was investigated in our study, considering that MPV alone may be a more valuable marker of inflammation.Methods: Between March 2017 and March 2018, COPD patients who applied to Abant Izzet Baysal University School of Medicine, Chest Diseases outpatient clinic were examined. Results were retrospectively scanned from patient files after institutional approval. Sixty-four (60.4%) stable COPD and 42 (39.6%) acute exacerbation COPD patients were included in the study.Results: Seventy-one (67%) of patients were male and 35 (33%) were female. NLR was 2.26 (0.93-6.48) in stable patients and 4 (1.18-36) in acute attack patients (p < 0.001); PLR was 137.44 (66.9-436.6) in patients with stable disease and 162.8 (85-1056.6) in patients with attack (p = 0.068). MLR was 5 (2.92-25) in acute attack patients and 4 (1.89-8.67) in stable patients; this difference was statistically significant (p = 0.003). MPV was found to be 7 (5.5-9.1) fL in patients with stable disease and 8 (5-13.4) fL in acute patients. This difference was statistically significant (p < 0.001). MPR was found to be statistically significantly higher in acute patients than in patients with stable disease (p = 0.04). WBC, neutrophil and CRP were found to be statistically significantly higher in acute patients than in stable patients (p < 0.05). There was a statistically significant correlation between WBC and NLR (r = 0.269, p = 0.005) and between CRP and NLR (r = 0.379, p < 0.001). Conclusions: Hemogram parameters from routine laboratory tests in COPD patients are cheap and easily accessible. It is important to detect the presence of subclinical inflammation in the stable phase, as well as to identify patients at risk of exacerbation. Prospective studies are needed to demonstrate correlations with inflammatory markers.